PENERAPAN METODE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DALAM MEDIA PEMBELAJARAN MULTIMEDIA KREATIF - Syarifah Eiva Fatdha; Marlis Alamsyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2020)
In today's technological developments, it is certain that every activity in human life has taken advantage of the role of technology, including in the world of education. However, there are still many schools that have not implemented technology as a means of supporting education, in general the existing learning models still convey material through traditional methods. So that it has a direct impact on students, namely by lack of student interest in learning, student activity is less and tends to be passive and learning outcomes are low. To improve this, the researchers applied creative multimedia learning media and used the Student Teams Achievement Division (STAD) method. This research was an action research using multimedia. Each meeting includes stages including planning, implementing actions, observing and reflecting. Through the application of a creative multimedia learning model using the Student Teams Achievement Division (STAD) method, it is hoped that it can improve teacher skills, student activities and learning outcomes for elementary school students in general and in learning. The application of the learning model can be used as a solution to improve the quality of learning in certain subjects.